Rare variants in XRCC2 as breast cancer susceptibility alleles. Issue 10 (10th October 2012) - Hilbers, Florentine S; Wijnen, Juul T; Hoogerbrugge, Nicoline; Oosterwijk, Jan C; Collee, Margriet J; Peterlongo, Paolo; Radice, Paolo; Manoukian, Siranoush; Feroce, Irene; Capra, Fabio; Couch, Fergus J; Wang, Xianshu; et al.
Abstract : Background: Recently, rare germline variants in XRCC2 were detected in non-BRCA1/2 familial breast cancer cases, and a significant association with breast cancer was reported. However, the breast cancer risk associated with these variants needs further evaluation. Methods: The coding regions and exon–intron boundaries of XRCC2 were scanned for mutations in an international cohort of 3548 non-BRCA1/2 familial breast cancer cases and 1435 healthy controls using various mutation scanning methods. Predictions on functional relevance of detected missense variants were obtained from three different prediction algorithms. Results: The only protein-truncating variant detected was found in a control. Rare non-protein-truncating variants were detected in 20 familial cases (0.6%) and nine healthy controls (0.6%). Although the number of variants predicted to be damaging or neutral differed between prediction algorithms, in all instances these categories were evenly represented among cases and controls. Conclusions: Our data do not confirm an association between XRCC2 variants and breast cancer risk, although a relative risk smaller than two could not be excluded. Variants in XRCC2 are unlikely to explain a substantial proportion of familial breast cancer.